Is enterprise education relevant to social enterprise?. Issue 8 (9th November 2015) - Bridge, Simon
Abstract : Purpose: – Both enterprise education and social enterprise have become fashionable but what, if any, should be the connections between them? The purpose of this paper is to explore those connections and to reflect on what relevance the two concepts might have for each other. Design/methodology/approach: – Both enterprise education and social enterprise have a number of different interpretations. Therefore those ranges of interpretation are first considered and then compared to see what there might be in common between the two concepts and to identify the desirability and practicability of linking them. Findings: – If enterprise education focuses on a narrow, private sector, business-creation interpretation of enterprise, and if the advocates of social enterprise insist on clearly separating it from other enterprises, then there will be little connection between the two. But if enterprise education takes a wider view of enterprise as part of life skills, and if social enterprise is seen as essentially enterprise, albeit with social objectives, then there is a clear case for linking the two and including social enterprise in enterprise training. Practical implications: – The implications of these conclusions are that, while some interpretations of enterprise education and social enterprise may suggest that they have little common ground, interpretations which link the two, and therefore the deliberate adoption of such interpretations, may actually be beneficial for the practice of both. Originality/value: – Little of the existing literature on enterprise education and social enterprise links the two concepts. This paper seeks to rectify that.